“The Women of Ancient Egypt”: vida y obra de Ella Satterthwait, pionera en el continente americano de los estudios sobre la mujer egipcia antigua - Castañeda Reyes, José Carlos (El Colegio de México, 2015)
Miss Ella Satterthwait (1884-1940) was one of the first Egyptologists in the USA, more specifically at the University of Chicago, and probably the first woman in the Americas to write about the subject of “women in ancient Egypt”. Her Ph.M. thesis reviewed the principal topics about this subject. Miss Ella’s thesis very probably was directed by Prof. James Henry Breasted, who had just returned from his field work in Egypt and, because of a variety of circumstances both professional and personal had to remain in Chicago following his important exploration work in Egypt. Miss Ella wrote, in fact, a specialized article —if we think in modern standards— which was an important contribution to this subject. Her research methodology and conclusions are very similar to the studies which followed on this important subject. But Miss Ella could not continue her formation as a professional Egyptologist. Her “micro-history” of life is a good example of the difficulty that women —in the USA as well as other countries— faced at the beginning of the last century when struggling to leave behind “the feminine mystique” or “womanly ideal” and to insert themselves into academia.